The Transmission of Islamic Messages in Local Social Space Through Artistic Approach - Agus Ahmad Safei (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This study aims to analyze the use of an artistic approach in transmitting Islamic messages by Kyai Zen, a popular da’i (da’wah actor) in West Java in the last 50 years. The process of conveying Islamic values will always be in the local social sphere where the da'wah is conveyed. As a process, the transmission of Islamic messages, or da'wah, can be done through an artistic approach by considering the socio-cultural dimensions of the da'wah target. This kind of approach is considered relevant especially because da'wah is aimed at instilling values, and not just informing something about religious teachings. The method used in this research is phenomenology about the actor of the da’wah who uses art as his preaching approach. This research seeks to reveal and study things that are typical of the phenomenon, as well as in the socio-cultural context of what kind of process of communicating Islamic messages takes place. As an analysis tool, this study uses Melvin DeFleur's Simultaneous Transaction Model. The results show that the process of transmitting Islamic messages through an artistic approach can be described as something unique and distinctive. This research also proves that the artistic approach taken by Kyai Zen in conveying Islamic messages finds compatibility and can be accepted by the people of West Java, and appears to be politer to invite people, but still friendly to local socio-cultural conditions.